The parameter space of hydrogen content added to Ar-nitrogen sputtering gas and substrate bias voltage for the formation of cubic boron nitride thin film deposited by unbalanced magnetron sputtering method - Ko, J. -S.; Park, J. -K.; Lee, W. -S.; Baik, Y. -J. (ELSEVIER SCIENCE SA, 2013)
The parameter space for the formation of cubic phase of boron nitride thin films as a function of substrate bias voltage and hydrogen content added to Ar-N-2 reactive sputtering gas was proposed. Cubic boron nitride (c-BN) films were deposited by unbalanced magnetron sputtering (UBM) method. Thin (100 mu m) Si strips (3 x 40 mm(2)) were used as substrates. A boron nitride target was used, which was connected to a radio frequency (RF) power supply set at 400 W. High frequency power connected to a substrate holder was used for self-biasing of up to -110 V. The deposition pressure was 0.27 Pa with a flow of Ar (18 sccm) - N-2 (2 sccm) mixed gas irrespective of hydrogen addition. Hydrogen gas up to 16 sccm was added to the Ar-N-2 mixed gas. The addition of hydrogen tended to decrease the threshold substrate bias voltage for c-BN formation. Even under low bias voltage, where only hexagonal boron nitride (h-EN) formed under the Ar-N-2 gas atmosphere, c-BN began to form with the addition of hydrogen to the gas. The surface of the film was very flat irrespective of the amount of added hydrogen. The deposition rate reduced with increasing hydrogen content. The residual stress decreased to 2 GPa with a hydrogen flow of 10 scan, while maintaining the c-BN fraction in the film above 60%. The role of the hydrogen during the c-BN formation was briefly discussed. (C) 2013 Elsevier B.V. All rights reserved.
Keywords: RESIDUAL-STRESS; VAPOR-DEPOSITION; HIGH-QUALITY; CBN FILMS; COATINGS; BN; FLUORINE; GROWTH